1991
DOI: 10.1128/aac.35.6.1254
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inhibition of hepatitis B virus DNA polymerase and cellular DNA polymerases by triphosphates of sugar-modified 5-methyldeoxycytidines and of other nucleoside analogs

Abstract: Of a series of 14 nucleoside 5'-triphosphates, those of 2',3'-dideoxy-3'-fluoro-5-methylcytidine, 3'-azido-2',3'-dideoxy-5-methylcytidine, 2',3'-dideoxy-3'-fluoroguanosine, 2',3'-didehydro-2',3'-dideoxy-5-methylcytidine, 2',3'-dideoxy-3'-fluoro-5-ethylcytidine, and 2',3'-dideoxy-3'-fluoroadenosine emerged as the most potent inhibitors of hepatitis B virus DNA polymerase (50% inhibitory dose, 0.03 to 0.35 microM). In contrast, cellular DNA polymerases proved to be resistant to (alpha) or partially affected by (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Table 1 summarizes these data and shows the percentages of the three phosphorylated species of nucleotides present before (0 min) and after (30 min) incubation in the presence of DHBV core preparation. However, for the subsequent experiments presented in this paper, dGTP and dATP were added at a concentration of 50 M, which is in great excess of the K m for the nucleotides (0.1 to 0.2 M) (14,21).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes these data and shows the percentages of the three phosphorylated species of nucleotides present before (0 min) and after (30 min) incubation in the presence of DHBV core preparation. However, for the subsequent experiments presented in this paper, dGTP and dATP were added at a concentration of 50 M, which is in great excess of the K m for the nucleotides (0.1 to 0.2 M) (14,21).…”
Section: Resultsmentioning
confidence: 99%
“…Modified dNTPs commonly exhibit a reduced level of uptake by DNA polymerases (10,(14)(15)(16)(17). Although certain modified dNTPs have been successfully used in PCR (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)21), accurate and comprehensive studies of their effects on rate and yield of DNA synthesis are rare.…”
Section: Substrate Properties Of Base-modified Dntps In Pcrmentioning
confidence: 99%
“…DNA polymerases are less able to accommodate modification of the sugar moiety in nucleotides (15). Many such modifications inhibit viral DNA polymerases, making these compounds interesting drug candidates for medicinal chemistry studies (16,17).…”
mentioning
confidence: 99%
“…In view of the experience that some nucleosides with the unnatural ␤-L configuration were more powerful and selective antiviral agents than their corresponding ␤-D isomers, we synthesized and evaluated the corresponding opposite optical isomers of some of the ␤-D-MetCdR derivatives that we studied several years ago. These investigations have shown that the triphosphates of some of the ␤-D-MetCdR derivatives are extremely powerful inhibitors of HBV DNA polymerase in vitro (e.g., ␤-D-3Ј-FMetdCTP [IC 50 , 0.03 M]) (20), though they proved to be less active under cell culture and in vivo conditions (19,21). Now we found for the corresponding ␤-L analogues that ␤-L-FMetCdR, ␤-L-ddMetC, ␤-L-d4MetC, and ␤-L-araMetC as well as their triphosphates were unable to inhibit either HBV replication in HepG2.2.15 cells or cell-free HBV DNA polymerase activity (EC 50 , Ն50 M; IC 50 , 1.9 M to 10.8 M).…”
Section: Discussionmentioning
confidence: 99%